Fruit vinegar : a diversified fruit product - Garg, Neelima; Kumar, Sanjay (Indian Horticulture, 2019)
Fruit vinegar contains antioxidant, which helps control blood glucose levels and weight loss. It may be effective in treating high cholesterol and inhibits tumour growth. It may help promote heart health and prevents infections caused by bacteria, viruses and yeast. It helps in allergies and reduces acid reflux and heartburn. Vinegar also helps patients having Alzheimer’s disease and dementia and prevents kidney stones and urinary tract infections. It can be used as all purpose cleaner and deodorizer and as facial toner and hair conditioner. It has use in fruit fly trap, as disinfectant and stain remover etc.